Plant Hormone-Mediated Regulation of Heat Tolerance in Response to Global Climate Change - Li, Ning; Euring, Dejuan; Cha, Joon Yung; Lin, Zeng; Lu, Mengzhu; Huang, Li-Jun; Kim, Woe Yeon (Frontiers in Plant Science, 2021)
Agriculture is largely dependent on climate and is highly vulnerable to climate change. The global mean surface temperatures are increasing due to global climate change. Temperature beyond the physiological optimum for growth induces heat stress in plants causing detrimental and irreversible damage to plant development, growth, as well as productivity. Plants have evolved adaptive mechanisms in response to heat stress. The classical plant hormones, such as auxin, abscisic acid (ABA), brassinosteroids (BRs), cytokinin (CK), salicylic acid (SA), jasmonate (JA) and ethylene (ET), integrate environmental stimuli and endogenous signals to regulate plant defensive response to various abiotic stresses, including heat. Exogenous applications of those hormones prior or parallel to heat stress render plants more thermotolerant. In this review, we summarize the recent progress and current understanding of the roles of those phytohormones in defending plants against heat stress and the underlying signal transduction pathways. We also discuss the implication of the basic knowledge of hormone regulated plant heat responsive mechanism to develop heat-resilient plants as an effective and efficient way to cope with global warming.